The influence of psychological guidance and exercise on the innovation and practice of English-Chinese translation teaching - Dan Xu , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Mental health (MH) issues are prevalent among college students (CS), and with the quick changes in today's culture, family, school, and other variables play a role. Under the influence, Children are subjected to various psychological stresses in their studies and daily lives, which has a detrimental effect on their healthy lifestyle and learning. This study aimed to investigate the influence of psychological counseling and exercise on the invention and practice of English-Chinese translation (ECT) instruction. This study indicated that physical activity has a good influence on the mental health of college students. This study assessed the class attention of CS before and after psychological counseling and exercise intervention using the attention stability test scale, the attention concentration test scale, and the visual tracking ability test scale. Significant differences exist between CS before and after exercise and two months after the experiment, as well as between the concentration and before the experiment. The visual tracking ability of college students before and after the exercise and two months after the experiment is still considerably different from that before the trial.\